JENIS-JENIS SERANGGA DAN FAUNA TANAH PADA LAHAN GARAPAN PASCA PENGAPLIKASIAN INSEKTISIDA APPLAUD 10 WP DIPERUMAHAN - Yohanes P. K. Narek; Paulus Taek; Nikmah Nikmah (SINERGI : Jurnal Riset Ilmiah, 2026)
Insects and soil fauna play a crucial role in maintaining the balance of the soil ecosystem and serve as indicators of environmental quality. The use of insecticides in land management has the potential to impact the presence and diversity of soil fauna. This study aims to identify the types of insects and soil fauna found in cultivated land after the application of the insecticide Applaud 10 WP in the Maulafa Housing complex, Kupang City. This study used a qualitative descriptive method with a survey or exploration technique. Soil and litter samples were taken at various depths, then extracted using a Tullgren funnel and identified in the laboratory. Environmental parameters measured included soil pH, temperature, and soil moisture. The results showed that 14 species of insects and soil fauna were found at the study site belonging to several orders and families, including Acari, Collembola, Coleoptera, Hymemoptera, Isoptera, and Chilopoda. The soil pH, temperature, and soil moisture values were within a range that is considered good for supporting soil fauna life. Based on these results, it can be concluded that despite the application of Applaud 10 WP insecticide, soil fauna was still found with a certain diversity. The presence of this soil fauna demonstrates its role in maintaining the fertility and balance of the soil ecosystem in residential areas